Analisis Disiplin Kerja Dalam Meningkatkan Kinerja Pegawai Pada Kantor Desa Nanjung - Gusti Aningsih, Khairani Rysda; Marselina, Resya Dwi (AkMen JURNAL ILMIAH, 2025)
This study aims to analyze the work discipline of employees at the Nanjung Village Office, Margaasih District, Bandung Regency, with a qualitative approach. Through the descriptive analysis method, data collection was obtained through observation, interviews, and documentation studies. The results of the study show that the level of work discipline of Nanjung Village Office employees can be said to be quite good, although there are several things that need to be improved, but the existing programs are still running smoothly and are still being implemented. This shows that despite some challenges, employees are still able to carry out their duties quite well, and efforts to improve the level of work discipline continue to be carried out gradually.